Variation of distances from mid-urethra to the obturator foramen: an MRI study - Hubka, Petr; Doumouchtsis, Stergios K; Berger, Mitchell B; DeLancey, John O (International urogynecology journal, 2012)
INTRODUCTION AND HYPOTHESIS: To estimate distances from the mid-urethra to the obturator foramina and to explore correlations between pelvic dimensions and body height. METHODS: This is a secondary analysis of a parent case-control study on the mechanisms of stress urinary incontinence. We measured pelvic dimensions on magnetic resonance images of women with (cases, n = 50) and without (controls, n = 50) stress urinary incontinence. RESULTS: The mean distance from mid-urethra to the obturator membrane among cases is 31.8 mm (left) and 32.1 mm (right), with a range from 25.9 to 42.0 mm. There were no significant differences in these distances when comparing left with right, or cases with controls. Weak correlation was found between the urethra-to-obturator foramina distances and heights only in the case subjects. CONCLUSION: There is high variability in the distance from mid-urethra to the obturator foramina. Height should not be used as a predictor of dimensions in the lesser pelvis.
Keywords: index tělesné hmotnosti; kyčel; design vybavení; Suburethral Slings; Urethra; suburetrální pásky; pánevní dno; Pelvic Bones; studie případů a kontrol; Body Height; Pelvic Floor; Equipment Design; Body Mass Index; magnetická rezonanční tomografie; Magnetic Resonance Imaging; uretra; ženské pohlaví; stresová inkontinence moči; Humans; pánevní kosti; Hip; Urinary Incontinence, Stress; Female; tělesná výška; lidé; Case-Control Studies